Study of the Effect of Changing the Frequency of Hello Messages on Quality of Service Parameters in the Reactive Protocol AODV - يوسف زينب (Latakia University Journal -Engineering Sciences Series, 2021)
The MANET mobile computer network is one of the most important types of networks that are practically and globally applied, and which receive increasing attention from researchers in this field, and this is due to the ease of installing, tuning and configuring their settings in a way that allows them to be established within a very short time that may not exceed a few seconds in some cases, in addition to that You do not need infrastructure such as coverage towers and access points, which means a significant saving in the material cost paid for building the network. In this research, the performance of the AODV protocol, which follows the class of Reactive networks, was evaluated according to a set of different scenarios in which the value of the interval between Hello Messages, which is sent by each node periodically, was changed in order to know its neighboring nodes, which are located at a distance One hop from it, and this is accompanied by a change in the number of network nodes in order to study the impact of this factor on various networks with light, medium and high load, and the simulation process was carried out using the NS2 network simulator program on the environment of the operating system UBUNTU with the evaluation of the results in terms of a set of parameters is the delay Time, packet delivery ratio and throughput